Effect of calcination conditions on phase formation and particle size of zinc niobate powders synthesized by solid-state reaction - Ngamjarurojana A. (2014)
A columbite-like phase of zinc niobate, ZnNb2O6, has been synthesized by a solid-state reaction via a rapid vibro-milling technique. The formation of the ZnNb2O6 phase in the calcined powders has been investigated as a function of calcination conditions by TG-DTA and XRD techniques. Morphology, particle size and chemical composition have been determined via a combination of SEM and EDX techniques. It has been found that single-phase ZnNb2O6 powders were successfully obtained for calcination condition of 600 °C for 2 h or 550 °C for 6 h with heating/cooling rates of 30 °C/min. Clearly, this study has demonstrated the potentiality of a vibro-milling technique as a significant time-saving method to obtain single-phase ZnNb2O6 nanopowders (∼50-300 nm) at low calcination temperature. © 2006 Elsevier B.V. All rights reserved.